STATIC GENERAL SOLUTION TO EINSTEIN’S FIELD EQUATIONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
We consider the Vaidya Tikekar metric; 3- dimensional space with time (t) being constant, in a super dense star which is spheroidal. We report a static general solution (in terms of hyper-geometric series) to Einstein's field equations using Vaidya-Tikekar metric.